Biased Volcanic Hazard Assessment Due to Incomplete Eruption Records on Ocean Islands: An Example of Sete Cidades Volcano, Azores - Kueppers, Ulrich; Pimentel, Adriano; Ellis, Ben; Forni, Francesca; Neukampf, Julia; Pacheco, José; Perugini, Diego; Queiroz, Gabriela (Frontiers in Earth Science, 2019)
It is well known that explosive volcanic eruptions pose serious hazards to local communities and may have worldwide impacts. However, the products of explosive eruptions on volcanic ocean islands are almost inevitably incompletely preserved as a significant portion of the erupted material is deposited into the ocean, thereby impeding our ability to accurately reconstruct past events, determine eruptive source parameters and ultimately assess the associated hazards. Sete Cidades is the westernmost central volcano of São Miguel Island, Azores. Although currently dormant, it has been the most active volcano on the island in the last 5 ky, with at least 17 trachytic explosive eruptions, some of which sub-Plinian, that took place inside the summit caldera. The last paroxysmal explosive eruption took place at ∼16 ka, enlarging the caldera to its present dimensions, and is recorded by the Santa Bárbara Formation. We here present evidence of a mid-distal deposit (>25 km from the vent) that can be correlated with the proximal (on Sete Cidades volcanic edifice) pumice fall deposit of the Santa Bárbara Formation based on deposit characteristics, textural features and geochemistry. This is the first evidence of a decimeter-thick deposit of Sete Cidades volcano in the central part of São Miguel Island, which allows to constrain eruptive source parameters and wind conditions. Given the predominant winds blowing from westerly directions, Sete Cidades is considered the most hazardous volcano for the entire island of São Miguel with its current population of >137,000 inhabitants. Most critically, the main harbor, only airport and hospital are located in the capital city of Ponta Delgada, ∼12 km SE from Sete Cidades caldera. In case of a future explosive eruption, under westerly blowing wind conditions, the impact on São Miguel could be catastrophic, with long-term economic consequences.